Effect of water ballast levels in the rear tires on tractor performance using disc plough on heavy clay soil - Zain, Omar Alnoor Ali Mohammed (Journal of agricultural, environmental and veterinary sciences, 2020)
This experiment was carried out at Masaad Center Farm for Technology Transfer and Training in Al-Gezira State in Sudan on heavy clay soil with a moisture content of 15.41%. To evaluate the effect of three levels of water ballast in the rear tires 25%, 50% and 75% and the effect of three different plowing depths 10, 15 and 20 cm with pressure constant (25 psi) in the rear tires. It was linked with disc plough of three discs. The split plot was used with three replications according to Randomized Block Design (RBD). The results were statistically analyzed using SPSS software. Rolling resistance force, draft force and fuel consumption were highly significantly affected (on 1% level) by the addition of different water ballast levels and tillage depth. The slippage ratio decreased by 15% when increasing the level of water ballast from 25% to 75% at a depth of tillage 15 cm. The rolling resistance increased by 43%, when increasing the water ballast levels from 25% to 75% at a depth of 20 cm. The water ballast levels increased from 25% to 75% at the depth of 10 cm the draft force was increased by 22%. Fuel consumption increased by 26%, when increasing the water ballast levels from 25% to 75% at the depth of tillage of 20 cm. The study showed that the addition of 75% water ballast level in the rear tires improves the performance of the tractor. The study showed that when the water ballast levels increased the fuel consumption, rolling resistance force and draft force were increased and slippage was decreased. As the depth of tillage increased, the slippage, fuel consumption, rolling resistance force and draft force were increased.
Keywords: water ballast levels; draft force; slippage; fuel consumption